Studi Komparatif Produktivitas Lahan Kopi Di Kabupaten Kepahiang - Utami, Dian Kurnia; Yusnida, Yusnida (Convergence: The Journal of Economic Development, 2022)
This study aims to find out what factors cause the difference in coffee land productivity in Merigi District and Muara Kemumu District, Kepahiang Regency. The data used were primary data taken directly from respondents using interview methods and questionnaires using the snowball sampling technique. Data analysis techniques that use the SPSS 25.0 program i.e. by application of chi square test and t-test. The results of the study using chi square test showed there were significant differences in the variables of production, land, number of trees, fertilizer amount and how to fertilize. For fertilizer type, education, plant age does not occur significant difference. And for the t-test for labor and capital, the significant difference between farmers in Merigi District and Muara Kemumu District. Where this in turn affects the differences in the productivity of the coffee grounds of the two regions.